(untitled) (Italian Review of Legal History, 2024)
The aim of the article is to present processes and changes that took place in the Polish People’s Republic in the early 1980s in connection with the activities of the Independent and Self-Governing Trade Union „Solidarność”. In this context, it is necessary to show how the then state authorities understood the rule of law (socialist or popular perceived through the prism of the views of Marx, Engels and Lenin). Taking into account the one party rule in Poland at that time, this article will analyze literature in the field of law. It will investigate, first, the writings of Jerzy Bafia, who for many years had an influence on shaping the law in Poland, first as president of the Supreme Court (1972-1976) and then as Minister of Justice (1976-1981). Second, this article presents an analysis of historical sources located in the Archive of Modern Records in Warsaw in the group entitled the Main Office of Control of Press, Publications and Performances in Warsaw. State censorship bodies during martial law in Poland influenced the discussion on the rule of law by controlling the press. Through censorship, the authorities attempted to weed out undesirable perceptions of the political system in Poland. From these documents, a picture emerges of the strategy of institutional censorship regarding the political and legal situation in the years 1981-1983.